Estudio fotoacústico de nanopartículas de oro y síntesis de nanopartículas de plata por ablación láser - Rivera Esteban, Jesús Manuel (2017)
ABSTRACT In this thesis, the morphology and size of the gold and silver nanoparticles obtained by laser ablation were investigated, with different reconfiguration methods. In the case of gold, the target was ablated with a pulsed Nd: YAG laser, (1064 nm, 37.48 mJ/p, 10 Hz, for 10 minutes), the absorption spectra show a single maximum absorption at 521 nm characteristic of the gold spherical nanoparticles. The PLI technique was applied to the colloids with laser pulses of 532 nm wavelength, 25.8 mJ of energy for 6 minutes. Dynamic light scattering (DLS) analysis showed that the NpsAu with PLI were 21 nm in diameter also, it was verified that the amplitude of the photoacoustic signal is directly and proportionally related to the concentration of NpsAu in the colloid evidencing that the greater The photoacoustic response is higher. For the case of silver, the target was ablated with a pulsed Nd: YAG laser (1064 nm, 10 ns, 15.7 mJ/p). The application of the focused PLI to the colloids with energy of 8.7 mJ/p and 1064 nm wavelength, showed that the NpsAg can change their spherical shape and size from approximately 10 to 15 nm in diameter to triangular with rounded corners of Approximately 48 nm sideways, which have been observed by scanning electron microscopy (SEM). In addition, the seed sowing method was used to study the morphology of NpsAg colloids whose characterization shows prismatic forms, pentagons and hexagons, these new configurations are shown by STEM images. From the research it was concluded that the focused PLI technique applied to colloids with NpsAg presents new morphologies. In the case of gold a change in size was found.